Periaqueductal Gray Afferents Synapse onto Dopamine and GABA Neurons In the Rat Ventral Tegmental Area - Omelchenko, Natalia (2010)
The midbrain central gray (periaqueductal gray; PAG) mediates defensive behaviors and is implicated in the rewarding effects of opiate drugs. Projections from the PAG to the ventral tegmental area (VTA) suggest that this region might also regulate behaviors involving motivation and cognition. However, studies have not yet examined the morphological features of PAG axons in the VTA or whether they synapse onto dopamine (DA) or GABA neurons. In this study, we injected anterograde tracers into the rat PAG and used immunoperoxidase to visualize the projections to the VTA. Immunogold-silver labeling for tyrosine hydroxylase (TH) or GABA was then used to identify the phenotype of innervated cells. Electron microscopic examination of the VTA revealed axons labeled anterogradely from the PAG, including myelinated and unmyelinated fibers and axon varicosities, some of which formed identifiable synapses. Approximately 55% of these synaptic contacts were of the symmetric (presumably inhibitory) type; the rest were asymmetric (presumably excitatory). These findings are consistent with the presence of both GABA and glutamate projection neurons in the PAG. Some PAG axons contained dense-cored vesicles indicating the presence of neuropeptides in addition to classical neurotransmitters. PAG projections synapsed onto both DA and GABA cells with no obvious selectivity, providing the first anatomical evidence for these direct connections. The results suggest a diverse nature of PAG physiological actions on midbrain neurons. Moreover, as both the VTA and PAG are implicated in the reinforcing actions of opiates, our findings provide a potential substrate for some of the rewarding effects of these drugs.